Analysis of extracurricular angklung material at ABA Karangwaru Kindergarten and ABA Blunyah Gedhe Kindergarten, Yogyakarta - Karissa, Violeta Chandra; Joko Pamungkas (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This study aims to evaluate the implementation of angklung extracurricular activities at TK ABA Karangwaru and TK ABA Blunyah Gede, Yogyakarta, in fostering the development of early childhood growth. Using a descriptive qualitative approach, data were collected through observations, interviews with instructors and teachers, and documentation. The results indicate that angklung activities effectively enhance fine motor skills, socio-emotional development, and cultural awareness in children. Children learn coordination through angklung play and gain collaborative experiences that strengthen their sense of responsibility and empathy. Challenges include short attention spans and varied motor skill levels. Strategies such as dividing children into smaller groups and providing positive reinforcement were employed to address these issues. In conclusion, angklung activities serve as an educational medium supporting early childhood learning principles, effectively nurturing interest and talent, and are recommended for broader implementation in other preschools.